Assessment of implantable drug delivery technology: poly (3-hydroxybutyrate) / polypropylene glycol films containing simvastatin - Dourado,Lays Fernanda Nunes (2021)
ABSTRACT Natural polymers have attracted much attention in recent years for the study of new drug delivery systems. These materials are used as polymer matrices to protect the active drug from degradation in the biological environment and to improve the release kinetics of the drug. The poly(3-hydroxybutyrate) (PHB) is a natural biocompatible polymer, widely used in combination with other polymers to improve their physicochemical properties. Thus, this work aimed to develop and characterize films of PHB and blends containing polypropylene glycol (PPG) with different concentrations of simvastatin (Simv.). The films were prepared by casting, dissolving PHB or a blend of PHB / PPG (90:10) and (5% or 25 %) Simv. in chloroform (2% w/v). The solutions were stirred for 3 h and then transferred to an appropriate glass mold for solvent evaporation for 48 h at room temperature. The obtained films were characterized by Fourier Transform Infrared (FTIR) spectroscopy, thermogravimetric analysis, scanning electron microscopy (SEM), optical microscopy, in vitro degradation study, and in vivo biocompatibility test. The results showed that PHB and blends of PHB / PPG are able to form a homogeneous film with the drug inside. A great amount of drug lead to the instability of polymeric matrixes and resulted in a facilitated film degradation. On the other hand, devices with 5% of Simv. were more stable, which suggests the application of these films for biomedical devices. In vivo studies revealed that the films can interact with the animals' organism, and do not undergo rejection. Hence, these films hold an innovative alternative in tissue engineering to promotes drug release by diffusion and erosion of the polymeric material.